Some Considerations about the Practical Importance of CJEU Judgements - Bufan, Radu; Șvidchi, Natalia (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
In this paper the authors analyse two CJEU judgments delivered as a result of preliminary questions in the VAT field sent by Romanian courts, with the purpose to outline the benefits of the preliminary ruling procedure, but also its drawbacks. It is the authors’ opinion that some of the general principles governing indirect taxes, as developed by the CJEU, could be used successfully in the field of direct, unharmonized taxes, especially when there are strong reasons in this regard. The judgment in case Zabrus Siret is a good example in this sense. On the other hand, the authors question the CJEU’s assessment of the facts of the case, considering the impact of such an assessment on the national referring court, by providing as example the judgement in case AJFP Caraş-Severin and DGRFP Timişoara.